Results of the in vitro study of the antibacterial activity of modifid magnesium alloy in experiments with E. coli and P. aeruginosa test-strains - V. M. Chornyi; N. M. Polishchuck; O. M. Kamyshnyі; M. L. Holovakha (Zaporozhye State Medical University, 2018)
The aim. To study the sensitivity of gram-negative microorganisms (the main pathogens of implant-associated infections) to the products of biodegradation of magnesium alloy ML-10, with subsequent justifiation for its use in traumatologic practice as artifiial implants with antibacterial activity. Methods. Magnesium alloy extract was prepared on the basis of Mueller-Hinton broth (pH 7.4). In sensitivity testing the reference test strains of Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853 were used. The bacteriostatic activity of the alloy extract was estimated by the presence or absence of the visual growth in test-tubes with microorganisms; bactericidal activity - by presence or absence of the growth of microorganisms colonies on cups with Mueller-Hinton agar after sowing from test tubes. The results of the study showed that the studied extract of magnesium alloy ML-10 shows high bacteriostatic and bactericidal activity with reference strains of E. coli and P. aeruginosa. The growth of this microorganisms on agar was observed only in test tubes, to which icroorganisms at a concentration of 109, 108, 107 CFU/ml were added the day before. The maximum growth of colonies on agar after sowing from these containers was recorded only after the fist day of incubation. During the incubation (37 °C) the number of colonies that grew in agar medium after the second and third sowing signifiantly decreased. Thus, the total number of E. coli colonies that grew after sowing on agar from tubes with the largest number of bacteria (109 CFU/ml) decreased from 220 (after the fist day of incubation in extract) to 2 colonies after 72 hours of incubation of flid in the thermostat, and from 192 to 1 colonies in experiments with P. aeruginosa. Similar results were obtained in experiments with lower microbial concentrations, which indicates high sensitivity of gram-negative microorganisms to ML-10 magnesium alloy extract. Conclusions. Magnesium alloy ML-10 in a liquid medium shows high bactericidal activity against gram-negative microorganisms, effctively suppressing the growth of reference strains of E. coli ATCC 25922 and P. aeruginosa ATCC 27853 during 72 hours.